Physical activity and food habits are associated with television time on weekends in Brazilian workers - Marina Christofoletti; Giovani Firpo Del Duca; Aline Mendes Gerage; Lisandra Maria Konrad; Elusa Santina Antunes de Oliveira; Mauro Virgílio Gomes de Barros; Markus Vinicius Nahas
Abstract Aims: Investigated the relation between eating habits or physical activity and weekend television viewing time, regardless of weekday television viewing in Brazilian workers. Methods: A representative cross-sectional study was conducted to measure the relation between weekend television viewing time and dietary indicators and physical activity across different domains in 47,477 workers. A questionnaire measured the time spent watching television per day on the weekend, physical activity indicators across different domains and eating habits. Absolute and relative frequencies and multinomial logistic regression adjusted were used to describe and identify the relationship between time spent watching television on the weekend and physical activity indicators or eating habits. Results: Workers who were physically active in the household (OR=1.09 [95%CI=1.04; 1.15] and OR=1.11 [95%CI=1.06; 1.16]) and leisure-time domains (OR=1.28 [95%CI=1.22; 1.35] and OR=1.30 [95%CI=1.24; 1.36]) were more likely to watch television ≥ 2 and ≥ 4 hours on a weekend day, respectively, than those watching television ≤ 1 hour/day. Consuming sweets (OR=1.30 [95%CI=1.22; 1.39]) and soft drinks (OR=1.11 [95%CI=1.03; 1.19]) was related to television watching ≥ 4 hours on a weekend day. However, workers who consumed fruits (OR=0.81 [95%CI=0.76; 0.85]) and vegetables (OR=0.91 [95%CI=0.86; 0.96]) daily were less likely to spend ≥ 4 hours watching television on a weekend day. Conclusion: We conclude that increased television viewing time on weekends, regardless of weekday television time, is related to leisure-time and household physical activity and with unhealthy eating habits in workers. Interventions focusing on the leisure-time may be an important alternative for health promotion in workplaces.